Rancang Bangun Sistem Informasi Pengaduan Fasilitas Publik pada Dinas PUPR Kabupaten Bima Menggunakan Prototyping dan Black Box Testing - Nur Anisa; Syarifuddin Syarifuddin; Hilyatul Mustafidah (Journal of Information System Research (JOSH), 2026)
The management of complaints regarding public facility damage at the Public Works and Spatial Planning Agency (Dinas PUPR) of Bima Regency currently faces challenges, specifically regarding the lack of optimal integration across the processes of report submission, verification, disposition, follow-up, and monitoring. This situation results in an unstructured complaint management process and hinders the monitoring of report handling progress. This research aims to design and develop a web-based Public Facility Complaint Information System capable of supporting structured complaint management aligned with the workflow of the Bima Regency PUPR Agency. The system development method employed is Prototyping, which allows for the evaluation and refinement of the prototype based on user feedback. System design utilizes the Unified Modeling Language (UML), encompassing Use Case Diagrams, Activity Diagrams, Entity Relationship Diagrams (ERD), and user interface design. The system is implemented using the Laravel framework and a MySQL database. System testing was conducted using the Black Box Testing method across 12 test scenarios covering core system functions—ranging from user management, complaint submission, verification, disposition, follow-up, and monitoring to report generation. Test results indicate that all 12 scenarios were executed successfully, yielding the expected outcomes with a 100% success rate. The contribution of this research is the creation of a complaint information system that integrates report submission via Village Operators, verification and disposition by the General Admin, follow-up by Division Admins, and monitoring by the Head of the PUPR Agency. Consequently, the designed and developed system facilitates a more structured, well-documented, effective, and easily monitored process for managing public facility complaints.